Fit & Shine Recreational Centre / Dg Rafidah Othman ... [et al.] - Othman, Dg Rafidah; Jafry, Nur Faezah; Ibrahim, Noor Nadia Natasha Dieyanna; Labadin, Sharrel Cassandra; Jinau, Jasmeen John; Mahouly, Effa Nur Syafiqah (2012)
Fit & Shine Centre was established under Blue Ivy Enterprise. We have decided to get involve in the service industry and chose fitness centre as our core business. Fitness centre always needed as a place for people especially young generation to spend their time to be healthy, fit and very enjoyable for every level of people, which is better than do something that will not give them any benefits. Fit & Shine Centre will be at 1 Jalan Sulaman,88400, Kota Kinabalu, Sabah. It is opposite of University apartment right side of Kingfisher Sulaman where also near to Taman Indah Permai. With a completion date of 2012, 1 Sulaman is within close proximity to universities and colleges so we have planned to attract more people to come. We have decided to start this business on one more year to go that is in the middle of 2013. We chose fitness centre as our main business because there are so many request from students and residents from those area also from Tuaran and its area, a place where they can relax and be healthy every time they need, so Fit & Shine Centre is the best place they could go for it. Fitness is not only for exercise but we also have sauna to relaxing every customer and other interesting programmes that we would like to serve as to achieve customers satisfaction and . This is the reason why we chose fitness compared to others as our business. Blue Ivy Enterprise is a partnership business. For our first business will use RM 500,000 to build up Fit&Shine Centre as we want to control the uses of money for better plan and strategic planning. We would like to loan from Public Bank with amount RM200,000 whereas RM300.000 by ours contribution. So, with the big amount of capital, our fitness centre will be different from the others. As the owners of Fit & Shine Centre, we expect to get profit more than what we have given. Furthermore, for our future plan, we decided to expand our business to other places such as rural area; urban area and any develop area with different type of programmes based on the area needs. We also plan to come up with jersey or T-Shirt for every customers, produce any technology that could enhance the quality of our company and other fitness items with our own label. We assure that Fit & Shine Centre will give new view and full satisfaction of fitness centre to our customers. Last but not least, we will stand in higher performance every chosen time and continually get higher satisfactions yet to be higher than our competitors.